In vitro and in vivo anti-hyperglycemia effects of extract of Faloak (Sterculia quadrifida R.Br.) leaves - Andrestia Dias, Velia; Celine Dinanda, Laurenza; Conrad Rambung, Charles; Dewi Puspitasari Tirtaningtyas Gunawan Puteri, Maria; Julianus, Jeffry; Hendra, Phebe (Pharmaciana, 2024)
Despite the availability of various conventional treatments, diabetes mellitus remains a serious global health concern with an increasing prevalence. This trend underscores the need to explore potential natural alternatives. Faloak, an indigenous plant of Indonesia, has been traditionally used for various health conditions, yet its potential as an anti-hyperglycemic agent has not been comprehensively investigated. This research focused on identifying the ingredients of Faloak leaves that could lower blood sugar levels and confirm these effects in laboratory and animal models. At various concentrations, the in vitro evaluation assessed the inhibitory effect of α-amylase and α-glucosidase enzymes. For in vivo evaluation, male mice were administered glucose, sucrose, and starch after being pretreated with Faloak leaf extract, and their blood glucose levels were monitored for 120 min. Faloak leaf extract demonstrated significant inhibitory activity against α-amylase and α-glucosidase enzymes. The IC50 values for sucrose and maltose inhibition were 30.37 and 65.36 mg/mL, respectively, while α-amylase inhibition showed an IC50 of 27.02 mg/mL. In the in vivo test, mice pretreated with the extract exhibited significantly decreased blood glucose levels at 120 min compared to the control group. These findings indicate that the ethanolic extract of Faloak leaves possesses promising anti-hyperglycemic activities, positioning it as a potential candidate for developing plant-based blood glucose management. Our results demonstrate that Faloak leaf extract exhibits substantial anti-hyperglycemic properties, inhibiting vital digestive enzymes and effectively reducing postprandial glucose levels. Identifying active ingredients paves the way for further research to elucidate specific bioactive compounds and their mechanisms of action